Responses to CAT at 50: reflections on accommodation from a sociolinguist - Meyerhoff, M (Elsevier, 2023)
Communication accommodation theory (CAT) has shown remarkable staying power. To what can we attribute this? I suggest several reasons: first, the general phenomenon of accommodation has been long recognised by researchers and skilled practitioners of language, hence a systematic approach predicated on clear principles and experimental methods was attractive to the fields of linguistics, social psychology of language and communication. Second, CAT researchers have adopted a syncretic approach to changes in focus and methods, building on and not rejecting previous stages of CAT. Third, CAT has proven amenable to both qualitative and quantitative methods. This last attribute has, I suggest, enabled it to be incorporated into sociolinguistic research on perception. I conclude with some reflections on how the social psychology of language and sociolinguistics differ in their objects of enquiry, and I look ahead to possible areas of synergies between the fields based on principles of accommodation theory.